IMPLEMENTASI KODE ETIK MAHASISWA TERHADAP KEGIATAN BELAJAR PERSPEKTIF HUKUM ISLAM DI IAI HASANUDDIN PARE - Fachrodin (Institut Agama Islam Hasanuddin Pare, 2024)
The student code of ethics plays an important role in maintaining student integrity and behavior in the academic process. At IAI Hasanuddin Pare, the student code of ethics is designed to support the creation of a conducive learning environment and motivate students to behave in accordance with academic norms. This article discusses the implementation of this code of ethics in teaching and learning activities at IAI Hasanuddin Pare, starting from applicable regulations, implementation in the field, to its impact on academic quality and student character development. Through a qualitative method with a case study approach, this research provides an overview of how the student code of ethics is practiced and integrated in the learning process. This research aims to analyze the implementation of the student code of ethics towards learning activities at the Hasanuddin Pare Islamic Institute (IAI). The student code of ethics is a behavioral guide that is expected to shape students' attitudes and morals in daily academic activities. This study uses a qualitative approach with a case study method, collecting data through interviews, observation and document analysis. The research results show that the student code of ethics at IAI Hasanuddin Pare is applied consistently in teaching and learning activities, although several challenges are still found, such as a lack of understanding by some students regarding the importance of the code of ethics and a lack of strict sanctions for violations. Apart from that, the implementation of the code of ethics has a positive impact on improving the quality of learning. Students who comply with a code of ethics tend to show higher discipline, responsibility and motivation in learning. As a result, the learning environment becomes more conducive and encourages the development of student character, such as honesty, work ethics and respect for others. However, there are some views that the application of the code of ethics is sometimes considered too strict by students, especially regarding the use of technology in class. The conclusion of this research is that although there are still obstacles in implementing the student code of ethics at IAI Hasanuddin Pare, the positive impact on students' learning activities and character development is very significant. The campus is advised to continue to increase students' understanding of the importance of a code of ethics and strengthen rule enforcement mechanisms to make them more effective.